Application of Bunchy TiO2 Hierarchical Microspheres as a Scattering Layer for Dye-Sensitized Solar Cells - Jiang, Yongjian; Zhao, Fengyang (Frontiers in Energy Research, 2021)
A novel bunchy TiO2 hierarchical microspheres composite nanostructure with strings of anatase TiO2 hierarchical micro-spheres and rutile nanobelts framework (HSN) was synthesized via an one-pot hydrothermal process. This new structure presents great specific surface area, large pore size distribution, homogeneous three-dimensional (3D) structure, high crystallinity and excellent light scattering performance simultaneously. The bi-layer photoanode film was successfully prepared which TiO2 P25 as absorption layer and HSN as an efficient scattering layer on the top of TiO2 P25 film in dye sensitized solar cells (DSSC). The bi-layer DSSC taken on a great progress in the power conversion efficiency (PCE) achieved 8.08%. However, the PCE of single and double layer TiO2 film DSSCs just showed 6.72% and 3.67% respectively. Such improvement was mainly because of the efficient scattering centers (HSN) which can bring the enhanced dye loading, fast charge transfer and excellent light harvesting efficiency.